Principles of Fluorescence Spectroscopy 2006
DOI: 10.1007/978-0-387-46312-4_8
|View full text |Cite
|
Sign up to set email alerts
|

Quenching of Fluorescence

Abstract: Two halide sensitive acridinium¯uorophores have been synthesised and immobilised in a hydrophilic copolymer. Thin ®lms of the copolymers swell in aqueous media allowing dye¯uorescence to be dynamically quenched by the di usion of halide ions. The new sensor ®lms have been characterised in terms of their sensitivity and selectivity towards halide and are compared to ®lms containing both bound and unbound Rhodamine B. The sensor ®lms are reversibly capable of determining halide ions at mildly alkaline pH with ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(15 citation statements)
references
References 314 publications
0
15
0
Order By: Relevance
“…Due to the absorbance of ct-DNA at 290 and 355 nm, though very small, which are the excitation and emission wavelengths for procaine, respectively, we have corrected the fluorescence data for the inner filter effect using the method described in ESI (eqn (S1)) † and given in established literature. 26 The corrected fluorescence data were than quantified with the help of Stern–Volmer equation which is given as: “where F 0 and F are corrected fluorescence intensities in absence and presence of quencher (procaine), respectively, and K SV is Stern–Volmer constant and [Q] is the concentration of quencher, K q is the bimolecular quenching constant and τ 0 is life time of fluorophore in the absence of quencher which is equal to the 5.7 × 10 −9 s −1 ”. 26,27 When quenching of fluorophore occurs by a quencher the mechanism is either static or dynamic.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the absorbance of ct-DNA at 290 and 355 nm, though very small, which are the excitation and emission wavelengths for procaine, respectively, we have corrected the fluorescence data for the inner filter effect using the method described in ESI (eqn (S1)) † and given in established literature. 26 The corrected fluorescence data were than quantified with the help of Stern–Volmer equation which is given as: “where F 0 and F are corrected fluorescence intensities in absence and presence of quencher (procaine), respectively, and K SV is Stern–Volmer constant and [Q] is the concentration of quencher, K q is the bimolecular quenching constant and τ 0 is life time of fluorophore in the absence of quencher which is equal to the 5.7 × 10 −9 s −1 ”. 26,27 When quenching of fluorophore occurs by a quencher the mechanism is either static or dynamic.…”
Section: Resultsmentioning
confidence: 99%
“…1a) provides means for monitoring the state of the aggregation probe in live cells by Fluorescence Lifetime Imaging Microscopy (FLIM). This methodology offers an accurate and absolute measure of the probe's state, free from the confounding effects of intensity calibrations and photo-bleaching 14,15,16 , thus removing the limits associated with the intensity-based readouts.…”
Section: Resultsmentioning
confidence: 99%
“…13 (8a-c, 8g, 9a-c, 9g; Table 4, entries 3-5,7,8-10,12). A survey of the literature revealed that electron-rich species, including substituted amino groups that can donate electrons to aromatic heterocycles (i.e., fluorophores), can act as potential fluorescence quenchers [66]. They are responsible for the formation of charge transfer complexes, which often return to the ground state without emitting a photon.…”
Section: Resultsmentioning
confidence: 99%